Enabling citizen-driven improvement of public services. Leveraging Tec hnology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank, 2015)
Effective public service delivery begins with knowing whether the serv ices offered are working as intended. We launched a system to enable c itizen input on the delivery of public services.